A study on consciousness of adolescent girls about their body image - Swati Dixit; G G Agarwal; J V Singh; Surya Kant; Neelam Singh (Wolters Kluwer Medknow Publications, 2011)
Background: Perceived body image is an important potential predictor of nutritional status. Body image misconception during adolescence is unexplored field in Indian girls. Objectives: To study the consciousness of adolescent girls about their body image. Materials and Methods: This multistage observational study was conducted on 586 adolescent girls of age 10-19 years in Lucknow district (151 from rural, 150 from slum, and 286 from urban area) of Uttar Pradesh, India. Information on desired and actual body size was collected with the help of predesigned questionnaire. Results: 20.5% of studied girls show aspiration to become thin, who already perceived their body image as too thin. 73.4% adolescent girls were satisfied with their body image, while 26.6% were dissatisfied. The dissatisfaction was higher among girls of urban (30.2%) and slum (40.0%) areas in comparison to rural (22.5%) area. Percentage of satisfied girls was less in the 13-15 years (69.9%) age groups in comparison to 10-12 years (76.5%) and 16-19 years (76.4%). Among girls satisfied with their body image, 32.8% girls were found underweight, and 38.4% were stunted. Underweight girls (42.1%) and stunted girls (64.9%) were higher in number within satisfied girls of slum area. Among all of these adolescent girls, 32.8% of girls had overestimated their weight, while only 4.9% of girls had underestimated their weight. Conclusions: This study concludes that desire to become thin is higher in adolescent girls, even in those who already perceived their body image as too thin.